2004
DOI: 10.1111/j.0730-7659.2004.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Literature on Postpartum Care: Selected Contraception Methods, Postpartum Papanicolaou Test, and Rubella Immunization

Abstract: Some evidence is available to support selected postpartum contraceptive methods and the postpartum rubella vaccine, but data are lacking on the effectiveness and optimal timing of the postpartum Pap smear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…15 Family planning can reduce maternal mortality by reducing the number of pregnancies, the number of abortions, and the proportion of births at high risk. 16,17 Almost one half of all pregnancies remain unintended.…”
Section: 14mentioning
confidence: 99%
“…15 Family planning can reduce maternal mortality by reducing the number of pregnancies, the number of abortions, and the proportion of births at high risk. 16,17 Almost one half of all pregnancies remain unintended.…”
Section: 14mentioning
confidence: 99%
“…One randomized trial evaluated the use of the postpartum Papanicolaou test at 4, 6, or 8 weeks following delivery. 20 The authors concluded that the longer time interval, or the 8 week interval, was associated with fewer false-positive tests as a result of decreasing inflammation. It should, however, be noted that many women have their only cytological screening during their perinatal visits.…”
Section: Normal Papanicolaou Test With or Without High-risk Hpv Deoxymentioning
confidence: 99%
“…21 The timing of the postpartum evaluation is based on the belief that around 6 to 8 weeks in the postpartum period, the inflammation associated with pregnancy has markedly decreased and therefore decreases the likelihood of false positive results on Papanicolaou test. 22 The importance of a thorough postpartum evaluation was illustrated in a retrospective study that identified 28 women with HSIL on a first trimester antepartum Pap smear. 3 All were followed with colposcopy and biopsy, as indicated, during pregnancy and at 6 to 8 weeks postpartum.…”
Section: Agc or Adenocarcinoma In Situmentioning
confidence: 99%